Effect of Activation Duration of Water Hyacinth-Based Activated Carbon Using Bilimbi (Averrhoa bilimbi) as an Activator on Free Fatty Acid Content in Crude Palm Oil (CPO) - Immawan , Mohd. Ackyl; Ratnawaty, Gervacia Jenny; Djohan, Herlinda; Imami, Ahmad Daudsyah (Public Health Frontier, 2025)
Crude palm oil (CPO) quality is significantly affected by its free fatty acid (FFA) content, which must be minimized to meet industrial standards and preserve oil stability. This study aimed to evaluate the effect of activation duration of water hyacinth-based activated carbon, using bilimbi (Averrhoa bilimbi) extract as a natural activator, on the reduction of FFA levels in CPO. A true experimental design was employed using activated carbon with activation times of 4, 8, 16, and 24 hours. A total of 30 CPO samples were tested, including untreated controls. The FFA content was determined using the alkalimetric titration method, and statistical analysis was conducted using ANOVA and linear regression. The results showed a consistent decrease in FFA content with increasing activation time: 9.38% (4 h), 6.32% (8 h), 6.29% (16 h), and 5.54% (24 h), compared to the control (12.54%). A significant negative correlation was found between activation duration and FFA levels (p = 0.000, β = –0.852), indicating improved adsorption performance over time. Although the 24-hour treatment yielded the greatest FFA reduction, levels remained slightly above the Indonesian National Standard threshold of 5.0%. These findings highlight the potential of water hyacinth-based activated carbon activated with bilimbi extract as a sustainable bioadsorbent, while also suggesting that further process optimization is needed to achieve industrial compliance.